2019
DOI: 10.1038/s41598-019-39001-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between eating behavior and poor glycemic control in Japanese adults

Abstract: This study investigated the relationship between eating behavior and poor glycemic control in 5,479 Japanese adults with hemoglobin A1c (HbA1c) <6.5% who participated in health checks. Respondents to a 2013 baseline survey of eating behavior, including skipping breakfast and how quickly they consumed food were followed up until 2017. We defined poor glycemic control after follow-up as HbA1c ≥6.5%, or increases in HbA1c of ≥0.5% and/or being under medication to control diabetes. We identified 109 (2.0%) respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…With respect to eating speed, the current findings are in agreement with previous research reporting that eating quickly is positively associated with hypertriglyceridemia [ 15 ], overweight [ 12 ] or obesity [ 18 ], gestational diabetes [ 44 ], and glucose intolerance [ 14 ]. In a three-year follow study involving 1314 Japanese university students ( n = 638 women), Yamane et al [ 13 ] showed that eating quickly was significantly associated with an increased risk of being overweight.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to eating speed, the current findings are in agreement with previous research reporting that eating quickly is positively associated with hypertriglyceridemia [ 15 ], overweight [ 12 ] or obesity [ 18 ], gestational diabetes [ 44 ], and glucose intolerance [ 14 ]. In a three-year follow study involving 1314 Japanese university students ( n = 638 women), Yamane et al [ 13 ] showed that eating quickly was significantly associated with an increased risk of being overweight.…”
Section: Discussionsupporting
confidence: 92%
“…Findings of previous research showed that eating quickly is a modifiable risk factor responsible for overweightness and obesity [ 12 , 13 ], poor glycemic control [ 14 ], elevated TG [ 15 ], and Mets [ 16 ] in different populations. By contrast, eating slowly was associated with healthy body weight [ 17 ] and less energy intake [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other independent variables were selected when the p-value was < 0.05 in the univariate model. Furthermore, Spearman's correlation analysis between each variable was performed, and variables with |r| > 0.8 were removed to avoid multicollinearity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal serum lipid levels were defined as triglyceride ≥ 150 mg/dL and/or HDL cholesterol < 40 mg/dL [21]. In addition, elevated CRP levels and poor glycemic control were defined as CRP ≥ 0.3 mg/dL [22] and HbA1c ≥ 6.5% [23], respectively.…”
Section: Different Variables Related To Dswmh Lesionsmentioning
confidence: 99%
“…Therefore, the participants who had a HbA1c level ≥6.5% were de ned as having poor glycemic control. In addition, participants who were using medication for diabetes were also included in the group with poor glycemic control since they had previously been diagnosed with diabetes already 24 .…”
Section: Measurement Of Hba1cmentioning
confidence: 99%